Inductive Approach Used in Teaching Speaking Skill: A Content Analysis - Mohammad Hoiruddin; Siti Maria Ulfa (Universitas PGRI Madiun, 2020)
This study aims to determine the feasibility of implementing an inductive approach in teaching speaking skills. The qualitative descriptive was used in this study by using content analysis technique. The technique of obtaining data used documentation. The data were analyzed by coding, display, and verification. The data analysis was carried out in depth by using some theories related to the inductive approach in teaching speaking skills. The results of the study indicate the interrelated of the implementation and responses of the students in using this approach. The results show that the inductive approach is very helpful for students in learning to speak English because it is based on the examples given and they have learnt to find patterns in English speaking. By seeing the examples, they also learn how to imitate the way how people say in English and they are actively involved in the teaching and learning process. Furthermore, it is suggested that inductive approach can be used in speaking class.